Słownictwo i styl prasowych tekstów o modzie (na przyktadzie „Elle” i „Twojego Stylu”) - Glapska, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2007)
The aim of the author was to show main tendemes in the vocabulary and style of press text about fashion. Having taken the material from “Elle” and “Twój Styl” the author noticed that the vocabulary and style of the texts about fashion becomes more poetic and more artistic.